Wall surface temperature calculation in the SolEdge2D-EIRENE transport code. (1st February 2016) - Denis, J; Pégourié, B; Bucalossi, J; Bufferand, H; Ciraolo, G; Gardarein, J-L; Gaspar, J; Grisolia, C; Hodille, E; Missirlian, M; Serre, E; Tamain, P
Abstract: A thermal wall model is developed for the SolEdge2D-EIRENE edge transport code for calculating the surface temperature of the actively-cooled vessel components in interaction with the plasma. This is a first step towards a self-consistent evaluation of the recycling of particles, which depends on the wall surface temperature. The proposed thermal model is built to match both steady-state temperature and time constant of actively-cooled plasma facing components. A benchmark between this model and the Finite Element Modelling code CAST3M is performed in the case of an ITER–like monoblock. An example of application is presented for a SolEdge2D-EIRENE simulation of a medium-power discharge in the WEST tokamak, showing the steady-state wall temperature distribution and the temperature cycling due to an imposed Edge Localised Mode-like event.